Optimization of the Kamsel Unit Performance of the Klaten Police Traffic Unit Through the Safety Riding Program for Traffic Accident Prevention - Wira Tri Nanda Putra Putra (Tanggon Kosala, 2022)
This research is motivated by the high number of traffic accidents in Klaten Regency. The Traffic Unit, in this case the Unit Kamsel, has carried out the Safety Riding Program to prevent traffic accidents. However, traffic accidents still occur frequently, this makes the authors interested in researching the problem of why the performance of the Klaten Police Satlantas Unit Kamsel through the Safety Riding Program to prevent traffic accidents has not been optimal. This study aims to describe the optimization of the Unit Kamsel's performance through the Safety Riding program and to describe the Safety Riding Program in preventing traffic accidents in the Klaten Police area. This research approach uses a qualitative approach, with data collection techniques of interviews, observation and study of documents. Meanwhile, the validity and reliability of the research data used a data triangulation technique using data analysis in the form of data reduction, data presentation, and conclusion drawing and data verification. The concept used is the concept of Safety Ridding using management theory (POAC) and organizational resource theory (4M). Based on the results of this study, (1) the Unit Kamsel's performance in preventing traffic accidents needs to be optimized through adding Unit Kamsel personnel, completing facilities and infrastructure, and updating the implementation method. The author provides advice by conducting training for personnel, asking for help from other units and making creative video competitions about Safety Ridding. (2) The Safety Ridding program in preventing traffic accidents is not optimal, therefore it is necessary to improve activity planning, activity implementation, and supervision in the implementation of Safety Ridding activities. The author provides suggestions by installing accident-prone warnings and creating data panels to facilitate supervision. The author concludes that the increase in traffic accidents is caused by several internal factors, namely planning activities, organizing personnel, implementing activities, and supervising personnel. While external factors, namely the low level of public knowledge and lack of understanding of knowledge about Safety Riding. However, the Safety Ridding program has not been implemented evenly to all levels of society.